Correction: Corrigendum: Rapid antibiotic-resistance predictions from genome sequence data for Staphylococcus aureus and Mycobacterium tuberculosis - Phelim Bradley (Nature Portfolio, 2016)
Nature Communications 6: Article number: 10063 (2015); Published: 21 December 2015; Updated: 20 April 2016 In Supplementary Data 3 of this Article, one of the Staphylococcus aureus accession codes is incorrect, as follows: SRR2101499 should be ERR1197981.